Pedagogy teachers’ competence establishes students’ digital ethics: Case of educational modernization in Indonesia - Fu, Wen Heng; Satrianawati, Satrianawati (International Journal on Education Insight, 2022)
This research aims to explore the competence of digital pedagogy of teachers towards the establishment of students’ digital ethics in the modernization of Indonesian education. This research uses the phenomenological approach to examine the essence of teachers' digital pedagogy competence. We collected the data using semi-structured interviews with five primary school teachers in Indonesia who have worked for more than three years. We chose the subjects based on their capability in guiding students in their routine. The results showed that the pedagogical teaching competence to establish the students’ digital ethics in education modernization are driven by some factors, namely: (1) the teachers have responsibility at work to self-actualize, (2) the teachers have high confidence to establish digital ethic in education modernization, and (3) the teachers use research and spiritual approaches to change the students’ ethics in education modernization. These three factors ultimately encourage teachers to establish digital ethics in education modernization. Therefore, it is important to establish the policy regarding the pedagogy digital competence. Furthermore, teachers can also take advantage of these findings by maximizing antecedent factors to increase digital pedagogy competence at work.